Exploring Theoretical and Conceptual Frameworks for the Enhancement of High-Order Thinking Skills through the Study of Thirukkural - Ponniah, K.; Safeek, N.M.M. (International Journal of Academic Research in Progressive Education and Development, 2024)
Thirukkural, authored by Thiruvalluvar, is a timeless masterpiece of classical Tamil literature, renowned for its enduring wisdom. This study aims to construct theoretical and conceptual frameworks for enhancing high-order thinking skills through the study of Thirukkural. Thirukkural covers diverse topics, including ethics, morality, governance, and love, offering a unique opportunity to foster high-order thinking skills such as critical thinking, creative reasoning, ethical decision-making, and problem-solving. The theoretical framework is rooted in the Transfer of Learning theory, which explores how learners apply existing knowledge and skills in new contexts. Thirukkural serves as a cognitive catalyst, facilitating thematic exploration, close reading, comparative analysis, critical and creative thinking, problem solving, analytical thinking, and practical application. These cognitive domains are essential for the development of high-order thinking skills. The conceptual framework outlines a structured approach for cultivating high-order thinking skills through Thirukkural. It encompasses thematic exploration, close reading and analysis, comparative analysis, critical thinking, creative thinking, problem solving, analytical thinking, and practical application. By immersing learners in these domains, educators can empower them with cognitive tools that transcend classroom boundaries, nurturing intellectual growth and meaningful engagement in various life contexts
Keywords: Classical Tamil Literature; High-Order Thinking Skills; Thirukkural; Transfer of Learning